A seasonal difference of daily energy expenditure in a free-living subterranean rodent, the silvery mole-rat (Heliophobius argenteocinereus; Bathyergidae) - Zelová, Jitka; Sumbera, Radim; Okrouhlík, Jan; Sklíba, Jan; Lövy, Matěj; Burda, Hynek (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2011)
In seasonal climatic regimes, animals have to deal with changing environmental conditions. It is reasonable to expect that seasonal changes are reflected in animal overall energetics. The relation between daily energy expenditure (DEE) and seasonally variable ecological determinants has been studied in many free-living small mammals; however with inconsistent results. Subterranean mammals, i.e. fossorial (burrowing) mammals which live and forage underground, live in a seasonally and diurnally thermally stable environment and represent a suitable model to test seasonality in DEE in respect to seasonal changes, particularly those in soil characteristics and access to food supply. Both factors are affected by seasonal rainfall and are supposed to fundamentally determine activity of belowground dwellers. These ecological constraints are pronounced in some tropical regions, where two distinct periods, dry and rainy seasons, regularly alternate. To explore how a tropical mammal responds to an abrupt environmental change, we determined DEE, resting metabolic rate (RMR) and sustained metabolic scope (SusMS) in a solitary subterranean rodent, the silvery mole-rat, at the end of dry season and the onset of rainy season. Whereas RMR did not differ between both periods, mole-rats had 1.4 times higher DEE and SusMS after the first heavy rains. These findings suggest that rainfall is an important environmental factor responsible for higher energy expenditure in mole-rats, probably due to increased burrowing activity. SusMS in the silvery mole-rat is comparable to values in other bathyergids and all bathyergid values rank among the lowest SusMS found in endothermic vertebrates.
Keywords: mikroftalmičtí podzemní hlodavci; druhová specificita; Species Specificity; energetický metabolismus; Seasons; Energy Metabolism; Mole Rats; zvířata; Animals; roční období